EFFECTIVENESS AND EFFICIENCY OF FINANCIAL MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDes) - Natila Angraeni; Musmulyadi Musmulyadi; Arwin Arwin; Rusnaena Rusnaena (Asy Syar'iyyah: Jurnal Ilmu Syariah dan Perbankan Islam)
This research aims to analyze the effectiveness and efficiency of financial management in the Village-Owned Enterprise (BUMDes) "Berkah" in Ajakkang Village, Soppeng Riaja District, Barru Regency. Employing a qualitative approach, data was collected through observation, interviews, and documentation. The results indicate that BUMDes "Berkah" has successfully met community needs through three main business units: Farmers' Shop, Stationery Business, and Savings and Loans. The Farmers' Shop improves farmers' access to quality agricultural inputs at affordable prices, the Stationery Business fulfills educational and office needs of the community, while the Savings and Loans provides financial access with low interest rates. However, significant challenges remain, including lack of transparency and accountability in financial reporting, limited stock, and limited public understanding of financial services. To enhance effectiveness and efficiency, increased transparency, training for managers, and improved promotional strategies are recommended. This study concludes that with further refinement, BUMDes "Berkah" can serve as an effective model for village economic empowerment in Indonesia.